Giving 2.0 transform your giving and our world - Arrillaga-Andreessen, Laura, 1970- (Jossey-Bass, 2012)
"Today's top strategies for individual donors to revolutionize their giving and the world. Major gifts may dominate headlines, but the majority of giving still comes from individual households. Even in 2009, at a time of deep recession, individual giving averaged almost $2,000 per household and 82% of the $300 billion donated that same year. Giving 2.0 empowers individual donors of every level navigating the seemingly infinite ways one can give. Based on her vast experience as a philanthropist, academic, and social innovator, Arrillaga-Andreessen shares the most effective techniques she herself pilots and studies. Draws from author's unique experience as founder/chairman of the Stanford Center on Philanthropy and Civil Society, founder/chairman of SV2 (Silicon Valley Social Venture Fund), and faculty member at Stanford Graduate School of Business. Helps individuals harness the power of technology, collaboration, advocacy, and social entrepreneurship to take their giving to the next level. Features dozens of stories on innovative methods of how individuals give time, money, and expertise, showing readers how they can renew their giving and reach their fullest potential. A practical and an inspiring call to action, Giving 2.0 is an indispensable tool for anyone aspiring to create significant change"--